EDUKASI DAN SKRINING MASALAH KESEHATAN MELALUI PEMERIKSAAN KADAR ASAM URAT PADA MASYARAKAT DESA TAMBOSUPA - Irma Irma; Kamrin; Harleli; Swaidatul Masluhiyah AF (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2026)
Gout is a degenerative disease that can attack productive age groups and the elderly. Gout that is not treated properly has the risk of becoming more severe, such as joint deformitus and causing more serious complications such as heart disease and kidney problems. This service activity aims to determine the prevalence rate of gout and to increase public knowledge about gout and its prevention. This service uses an implementation method, namely measuring uric acid levels and educating about gout and its prevention. This service activity was carried out in Tambosupa Village, Morama District, South Konawe Regency, Southeast Sulawesi Province with 26 participants. The service team consists of practical field learning (PBL) students and lecturers. From the results of this service it can be concluded that the prevalence rate of gout in Tambosupa Village is still quite high and this service can increase public knowledge about gout and prevention.